If it's not what You are looking for type in the equation solver your own equation and let us solve it.
q in (-oo:+oo)
(2/3)*q = (1/3)*q+9 // - (1/3)*q+9
(2/3)*q-((1/3)*q)-9 = 0
(2/3)*q+(-1/3)*q-9 = 0
1/3*q-9 = 0 // + 9
1/3*q = 9 // : 1/3
q = 9/1/3
q = 27
q = 27
| -8=7-x | | 120=38.14+0.50x | | x-2.3=2.3 | | 8x+4=9x-8 | | 11x=35 | | 2x^(4/3)-5x^(2/3)+2=0 | | a-4/2=8 | | (4x+1)+(2x-1)=5x | | 3+2y+5+4+3+5y= | | (a+n)^13/3*(a+n)^1/6 | | r-6/2=r+4/3 | | 2/3q=1/3q+7 | | y=(5x^2+6x+3)(4x^2-4x+5) | | 2x^4/3-5x^2/3+2=0 | | -0.10(17)+0.60x=0.05(x-12) | | (Y-4)-(y+5)=9y | | 5-4m=7 | | -36=x+-8 | | -2k+10(7+k)=10(k-7)+12k | | m+8/-3=17-m/-2 | | 55=20x-5 | | 7(1-x)-1=20 | | 6-15=z/-6 | | X/5-1=-9 | | 2/x+5-1/x-3=0 | | 25.1=2*3.14*x | | -310=12x-130 | | 64+32x=1800 | | 2x^2-8x-8y-32=0 | | 2/x+5-1/x_3=0 | | 6*11/2g-1 | | 3x-3(x-3)=2x-1*2x(2x-1) |